A new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from Montagne d’Ambre National Park, northern Madagascar - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2017)
A new species, Diastatotropis perrinae Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Cappadocini), from north Madagascar is described. Male genitalia are studied and illustrated and colour photographs are added. A comparison with the most similar known species, D. tigrinus Lacordaire, 1866, is provided.